2002
DOI: 10.2105/ajph.92.7.1096
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Use of Child Restraints in Motor Vehicles in a Hispanic Neighborhood

Abstract: The use of restraints in motor vehicles is less common in minority and low-income populations than in the general population. A preliminary survey of Hispanic preschool-aged children in west Dallas, Tex, conducted in 1997 showed much lower child restraint use (19% of those surveyed) than among preschool children of all races in the rest of the city (62%). Because there are few reports of successful programs to increase child restraint use among Hispanics, we undertook to implement and evaluate such a program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…Four studies were designed with selected control communities matched on demographic characteristics (Ebel et al, 2003;Guyer et al, 1989;Davidson et al, 1994;Decina et al, 1994) two studies compared the results from the intervention community to the rest of the geographical region (Istre et al, 2002) or country (Ekman et al, 2001) and a further two studies were designed with the intervention community acting as an historical control (Durkin et al, 1999;Roberts et al, 1988). Meta-analysis was not possible due to the diversity of the independent and outcome variables in each of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were designed with selected control communities matched on demographic characteristics (Ebel et al, 2003;Guyer et al, 1989;Davidson et al, 1994;Decina et al, 1994) two studies compared the results from the intervention community to the rest of the geographical region (Istre et al, 2002) or country (Ekman et al, 2001) and a further two studies were designed with the intervention community acting as an historical control (Durkin et al, 1999;Roberts et al, 1988). Meta-analysis was not possible due to the diversity of the independent and outcome variables in each of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed the same reduction in the control community injury rates as the intervention community (Davidson et al, 1994). Limitations in the evaluation methodology (Istre et al, 2002;Ekman et al, 2001) or conflicting results (Ebel et al, 2003;Decina et al, 1994) for the other four programs require their results to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The mandatory use of CSRS is an important legal factor but it is not enough for compliance. 6,7,11,18,19,24 Given low rates of CSRS use associated to slightly low rates of seat belt use by the drivers and the recent implementation of specific CSRS legislation, CSRS use is a challenge to preventive medicine in Brazil, requiring action focusing on raising awareness of safety transportation rules for children. Further studies are needed for developing strategies to promote CSRS use as a way to prevent injuries and deaths in children passengers of vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this research, interventions have been aimed at trying to increase the use of child restraints in motor vehicles in Latino communities. The most successful interventions, conducted in Spanish and English, incorporated child safety seats into the local culture and community by utilizing church leaders and Latino police and community workers and did not require a payment if the family could not afford it (52).…”
Section: Injury and Violence Preventionmentioning
confidence: 99%